The Influence Of Brand Image, Online Service Quality , And Of Use On Purchase Decisions On With Trust As A Mediation Variable - Rahayu, Suharni; Limakrisna, Nandan; Horas V. Purba, Jan (International Journal of Science, Technology & Management, 2023)
This research is to determine the effect of Brand Image, Online Service Quality, and Ease of Use on purchasing decisions with Trust as a mediating variable. The population in this study are consumers who have purchased products on the Shopee e-commerce application in South Tangerang. The sample used in this study were 225 respondents. The sampling technique used was purposive sampling. By using a quantitative descriptive approach. Data analysis used statistical analysis with SEM-PLS. The results of this study indicate that Brand Image has a positive and significant effect on Trust. Online Service Quality has a positive and significant effect on Trust. Ease of Use has a significant positive effect on Trust. Brand Image has a negative and insignificant effect on Purchasing Decisions. Online Service Quality has a positive and significant effect on Purchasing Decisions. Ease of Use has a positive and significant effect on Purchasing Decisions. Trust has a positive and significant effect on purchasing decisions.